Cultivation of seaweed Gracillaria sp. Using longline methods under different space of planting - Nurlaila Ervina Herliany; Zamdial Zamdial; Reza Meylia (Jurusan Akuakultur, Universitas Bangka Belitung, 2016)
One of the most species that using in seaweeds farming is Gracilaria sp. The success of farming, is determined by several factors such as plant spacing. The aim of this study is to determinine the best plant spacing for seaweeds farming and water quality of farming location. The study was held in the village of Kahyapu, Enggano Island, Bengkulu province from March until May 2015. The research was held using experimental methods that refers to Meylia (2015). Seaweeds is grown using three plant spacing (20, 25 and 30 cm) for 42 days. Wet weight of seaweeds was measured every week. Water quality was measured at the beginning, middle and end of the study. Data of wet weight and absolute growth rate were analyzed using a completely randomized design (CRD) factorial at the 95% confidence level with two factors, plant spacing and farming periode. Duncan Multiple Test (DMRT) was used if there is a significant difference. The results showed that the interaction between plant spacing and farming periode has siginificant effects to wet weight. Duncan test showed that more extensive planting space and the longer the cultivation, the wet weight will be higher. The rate of absolute growth is affected by plant spacing and observation times. Based on the Duncan’s test, wider spacing can increase the growth rate. Plant spacing of 30 cm is the best treatment. Water quality (temperature, salinity, pH, brightness and water current) during farming was suitable for seaweeds growth